Impact of pretreatment with P2Y12 inhibitors in patients with acute coronary syndromes without ST elevation. Analysis of 2 multicenter registries - Sigal, Alan R. (2023)
Objectives. To evaluate the rate of use of antiplatelet pretreatment in patients with non-ST elevated acute coronary syndrome (NSTEACS) and its association with adverse events in two Argentine registries. Materials and methods. We retrospectively analyzed two Argentine acute coronary syndrome (ACS) registries from 2017 and 2022. We explored the incidence of pretreatment and the drug used. We evaluated the relationship between this strategy and a composite clinical outcome of in-hospital events: death + myocardial infarction + stent thrombosis + post-MI angina + transient ischemic event/cerebrovascular event, and with bleeding events (BARC 2 or higher). Subsequently, we performed a multivariate analysis by logistic regression with other clinical variables. Results. A total of 1297 patients were included; 75.6% were men, 25.6% diabetics, 27.1% smokers, 70.3% hypertensive, and 23.1% had a previous ACS. The mean age was 55.3 years. The mean GRACE score was 113.5, and the CRUSADE was 23.8. 44% of the patients received pretreatment, the majority with clopidogrel (93.5%). Pretreatment was significantly associated with a higher incidence of the composite clinical outcome (10.1% vs. 6.9%) (OR 1,56; IC 95%: 1,06-2,3; p=0,02). Bleeding events were numerically more frequent with pretreatment (8.7% vs. 5.9%) (OR 1,51; IC95%: 0,99 -2,3; p=0,054). In the multivariate analysis, pretreatment was no longer associated with a higher incidence of ischemic outcomes (OR 1,4; IC95%: 0,89-2,3; p=0,13). Conclusion. Pretreatment was used in almost half of the patients, mainly with clopidogrel, and did not show a reduction in ischemic events in patients with NSTACS.